1999
DOI: 10.3171/jns.1999.90.1.0042
|View full text |Cite
|
Sign up to set email alerts
|

Risk of injury to cranial nerves after gamma knife radiosurgery for skull base meningiomas: experience in 88 patients

Abstract: Gamma knife radiosurgery appeared to be an effective method to control the growth of most skull base meningiomas in this intermediate-term study. The risk of trigeminal neuropathy seemed to be associated with doses of more than 19 Gy, and the optic apparatus appeared to tolerate doses greater than 10 Gy. Considering the risks to cranial nerves associated with open surgery for comparable tumors, the authors believe that gamma knife radiosurgery is a useful method for the management of properly selected recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(139 citation statements)
references
References 18 publications
7
126
0
6
Order By: Relevance
“…Consistent with our experience, Morita et al found one patient to have permanent new oculomotor palsy following application of 10 Gy to the cavernous sinus. 50 Prevailing reports stated that the fifth cranial nerve seems to tolerate doses of up to 20 Gy, 15 17 19 30 50 but the new onset of transient trigeminal neuralgia following administration of 12-17 Gy to the trigeminal nerve was observed in two patients of our series.…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with our experience, Morita et al found one patient to have permanent new oculomotor palsy following application of 10 Gy to the cavernous sinus. 50 Prevailing reports stated that the fifth cranial nerve seems to tolerate doses of up to 20 Gy, 15 17 19 30 50 but the new onset of transient trigeminal neuralgia following administration of 12-17 Gy to the trigeminal nerve was observed in two patients of our series.…”
Section: Discussionmentioning
confidence: 83%
“…However, there are certain restrictions associated with this technique. It is not possible to treat lesions with a diameter > 3.5 cm (21,22); in addition, treatment delivery in a single dose presents a risk of further deterioration in neuropathy (6,7,(22)(23)(24)(25)(26) that can result in loss of the optic nerve. Although the functional results of the various studies published show significant postoperative improvement, this is nevertheless not as impressive as the potential improvement offered by FSR.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of this treatment protocol (total dose, number of sessions, and dose per session) was based on the knowledge of optic nerve tolerance to single-session radiosurgery 22,23,27,28) and experience treating the anterior optic pathways and other cranial nerves with multisession radiosurgery 1,9,32) . The aim of fractionated stereotactic radiosurgery is to reduce radiation injury to the surrounding structures and to be able to make radiation field be broader.…”
Section: Discussionmentioning
confidence: 99%